Sexual Violence in Public Spaces: A Criminological Study of Social and Cultural Factors - Peter Guntara; Trias Pangesti; Yessa Ayu Agista (Westscience Press, 2026)
Sexual violence in public spaces continues to increase in both physical and digital spaces. This study aims to analyze the social and cultural factors that influence the occurrence of sexual violence and assess the implementation of law enforcement through a normative juridical approach. Using primary legal materials such as the TPKS Law, the Criminal Code, and sectoral regulations, as well as secondary legal materials such as criminology literature and academic studies, this study found that sexual violence in public spaces is influenced by the dominance of patriarchal culture, the normalization of aggressive sexual behavior, the practice of victim blaming, the weakness of the public space surveillance system, and the limitations of institutional responses. From a legal perspective, the TPKS Law provides a comprehensive legal basis for the prevention and handling of sexual violence, including reporting mechanisms, victim-friendly investigations, evidence-based electronic evidence, and victim recovery. However, its implementation still faces structural obstacles such as a lack of gender education, a lack of gender-responsive policies in public institutions, and a social culture that tolerates violence. These findings underscore the need for a holistic prevention strategy that combines law enforcement, gender education, strengthening the design of public spaces, and cultural change campaigns to create safe and gender-equitable public spaces.